Acute pharyngitis with the abrupt manifestation of neurological disorders, leading to a diagnosis of Neuro-Behçet's disease. Issue 1 (1st January 2021) - Yamagishi, Junya; Kagoya, Ryoji; Saito, Maki; Fujimoto, Chisato; Kikuchi, Hirotoshi; Ito, Ken
Abstract: Neuro-Behçet's disease (NBD) involves the nervous system and has a poorer prognosis. Since the typical delay in the onset of neurological symptoms is several years, difficulties are associated with diagnosing NBD when neurological disorders occur almost simultaneously with other major symptoms. We herein report a rare case of NBD that presented with the almost simultaneous manifestation of principal symptoms and neurological disorders. A 32-year-old Japanese woman presented with severe pharyngitis with a white coating and ulcers. On the third day of admission, she suddenly fainted while walking with urinary incontinence. T2-weighted MRI showed multiple high-intensity signals in the brainstem. Genital ulcers and pseudofolliculitis on the back were also detected. Stabilometry showed principal involvement of the peripheral vestibular system. A cerebrospinal fluid examination revealed an increase in the number of cells with lymphocyte dominance. The interleukin-6 level was markedly elevated. Pulse corticosteroid therapy led to the attenuation of symptoms.